Ectopia Cordis: a Rare Congenital Condition - Shrestha, Ramesh; Chhetri, S; Regmi, MC; Basnet, P (Nepal Journal of Obstetrics and Gynaecology, 2018)
Ectopia cordis is a rare congenital malformation and only few cases have been reported in literature previously. It is defined as the complete or partial evisceration of heart outside the thoracic cavity through the sternal defect. Most cases are sporadic. The classical presentation for the antenatal diagnosis on ultrasonography is a pulsating heart out of the thoracic cavity with absent chest wall. We reported three cases of ectopia cordis in the last one and half year in our institute. Two of them were diagnosed on ultrasound and the third case terminated for meningocele with severe oligohydramnios had associated ectopia cordis detected after delivery. All three were admitted via out patient department for termination. The first case live at birth had isolated thoracic ectopia cordis with birth weight of 2.4 kilograms, Apgar score of 7,8,9 and was delivered by caesarean section for failed induction while the other two were still birth and had thoraco-abdominal ectopia cordis. The live baby was taken to Sahid Gangalal hospital in Kathmandu by the visitors after two days of delivery and the baby underwent surgical intervention but had an unsuccessful outcome. Regarding the management of this condition, parental counseling for pregnancy termination is advised. Though few cases of surgical interventions for ectopia cordis have been reported, mortality rate is still very high.